Sensor validation and Fieldbus - Henry, M (Institution of Engineering and Technology, 1995)
Intelligent sensors are now able to generate diagnostic messages, and Fieldbus can carry them, but how are they to be integrated into a control system? It is argued that a standard format must be adopted, and online uncertainty is proposed as a metric for data quality.